PROSPEK PENGEMBANGAN KOMODITI JAGUNG DI KECAMATAN BLULUK KABUPATEN LAMONGAN - Djohan Budiman; Eri Yusnita Arvianti; F. Kasijadi (Universitas Tribhuwana Tunggadewi, 2011)
Bluluk District is known as a production centre of maize in Lamongan Regency. However, the optimum maize production in this area not has not been met. This study was aimed to (a) implementation of agribussiness system in developing maize, (b) trend of harvesting area and maize yield, and (c) policies supporting maize development. This study was conducted from August 2009 – January 2010. Samples selected for this study comprised 30 farmers. The collected data were primer and secunder and the data to analyses with Qualitative-descriptive, Trend and SWOT. Results of this study showed that: (1) agribusiness system for maize development has not been maximally implemented, (2) trends of harvest area and production of maize were linear and tended to increase every year, and (3) the policy strategies for maize development using agribusiness approach consist of several aspect: (a) production, (b) institutional, (c) financial, (d) harvest technology, (e) marketing, and (f) human resource